Small plates : short fiction - Page, Katherine Hall (Page, Katherine Hall. Faith Fairchild mystery., 2014)
"Agatha Award winner Katherine Hall Page presents a book of short stories featuring her famed heroine Faith Fairchild. For years, Katherine Hall Page has delighted readers with her Faith Fairchild series, each book like a delicious, satisfying meal. Now, Page has whipped up a tasty collection of appetizing bites. In "The Body in the Dunes," Faith's vacation offers more excitement than she and her husband bargained for when a terrified woman knocks on their hotel room door looking to hide from her husband. A case hits close to home in "The Proof is Always in the Pudding," when Faith investigates a generations-old superstition that has been passed down in her husband's family. Faith and her sister, Hope, counsel a bride-to-be suffering a number of alarming "accidents" before the big day in "Across the Pond." In "Sliced," Faith switches from contestant to detective when a killer reality television cooking competition turns deadly. Small Plates also includes some irresistible standalone treats, including the Agatha Award-winning "The Would-Be Widower," about a husband who longs to be rid of his wife, and "Hiding Places" in which a young wife's new husband may not be all that he appears" --